PEMBUATAN PERANGKAT PEMBELAJARAN TARI MELAYU BERBASIS HIGH ORDER THINKING SKILLS (HOTS) UNTUK SISWA/I KELAS VIII SMP NEGERI 1 TANJUNG TIRAM - Jefri Jefri; Yusnizar Heniwati (Gesture: Jurnal Seni Tari, 2020)
ABSTRACTThis research aims to make learning tools for Malay Dance based on High Order Thinking Skills (HOTS) for students of class VIII of SMP Negeri 1 Tanjung Tiram. This study uses theories related to topics such as packaging theory, learning, teaching materials in the form of textbooks and HOTS-based student worksheets. The main theory used in this thesis uses the theory of Andi Prastowo (2014: 17) which states that "Teaching materials are all materials (both information, tools, and texts) that are arranged systematically which displays a complete figure of competencies that will be mastered by students and used in the learning process with the aim of planning and analyzing learning implementation, and Widjajanti's theory (2008: 1) LKS is one of the learning resources that can be developed by the teacher as a facilitator in learning activities, LKS that are arranged can be designed and developed according to conditions and HOTS (Yuniar, et al: 2015) is a thinking ability that tests at a higher level, in the sense that students not only memorize and remember, but must be able to analyze, synthesize, and evaluate. This study uses a qualitative method. The object in this study is the Malay Dance learning tool based on High Order Thinking Skills (HOTS). This research was conducted in May to August 2019, the data obtained were analyzed using qualitative data analysis. The location of this research was carried out in one of the schools in Batu Bara Regency, namely SMP Negeri 1 Tanjung Tiram, located at Jl.Sekolah Sukamaju Village, Tanjung Tiram District, Batu Bara Regency, North Sumatra. The results of this study are in the form of teaching material products in the form of a Malay dance textbook (Dua Song Dance) and Malay Dance Student Worksheet (LKS Dance) in the subject of cultural arts (dance) related to Malay Dance material (Song Dance Two). The packaging of this learning tool was prepared by adjusting the syllabus and Learning Implementation Plan (RPP) for students of class VIII with basic competencies 3.1 understanding the uniqueness of traditional dance moves based on floor patterns using dance support elements. The preparation of this learning tool is designed as for the achievement of learning outcomes both cognitive, affective and psychomotor.Keywords: Learning tools, Malay dance, High Order Thinking Skills (HOTS)